Fake news nas redes sociais: a importância da educação midiática - LEÃO, Gleycy Kellen Gomes (2023)
The present research has the title “The Fake News in social networks: The importance of media education”. Through a narrative research, we have as general objective: to understand the importance of media education as an aid in the process of identifying false information. As specific objectives, the following are defined: identifying how Fake News undermines decision-making processes, discussing how education for the media influences the process of identifying online news and pointing out how cyberculture impacts the lives of the Brazilian population. We raised the hypothesis that people learn from media production processes and from social networks – they develop a more critical reading and a differentiated interpretation of facts. Thus, the problem stems from the question: How is media education being addressed in classrooms according to academic publications on the subject? However, it was possible to identify that there are debates about fake news and the importance of media education, but further discussions on the subject presented are still needed, as well as publications of works in this axis.